Late Onset and Persistence of Post-Traumatic Stress Disorder Symptoms in Survivors of Critical Care - Aaron Khitab; John Reid; Vern Bennett; G Camelia Adams; Lloyd Balbuena (Canadian Respiratory Journal)
BACKGROUND: Several recent studies have reported that post-traumatic stress disorder (PTSD) is a frequent occurrence in survivors of an intensive care unit (ICU) admission.